2006
DOI: 10.1111/j.1741-6248.2006.00076.x
|View full text |Cite
|
Sign up to set email alerts
|

Dancing With Giants: Acquisition and Survival of the Family Firm

Abstract: In this article, we examine the responses of family companies to the emerging environment of mergers and acquisitions, specifically within the international wine industry. At issue is the question of how the family perspective influences responses of a family firm to the prospect of merger or takeover. We examine the issue through a case study of the takeover of an Australian wine producer and family firm, Peter Lehmann Wines. The case study demonstrates ways in which the family perspective is critical in driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 25 publications
(29 reference statements)
0
37
0
Order By: Relevance
“…This phenomenon of following the guidelines and basing decisions on the principles laid down by the founder is called 'founder legacy centrality' (Kelly et al, 2000). It is important that family firms see to it that the founder legacy is carried over in acquisitions to demonstrate the commitment and sincerity of the family owners (Steen and Welch, 2006). In order to sustain the founder legacy, it is of strategic importance that a member of the family takes over in the succession of the business, as he/she usually has a lifelong knowledge of the firm and a historical liaison with suppliers, clients and staff (Royer et al, 2008).…”
Section: Founder Legacymentioning
confidence: 99%
“…This phenomenon of following the guidelines and basing decisions on the principles laid down by the founder is called 'founder legacy centrality' (Kelly et al, 2000). It is important that family firms see to it that the founder legacy is carried over in acquisitions to demonstrate the commitment and sincerity of the family owners (Steen and Welch, 2006). In order to sustain the founder legacy, it is of strategic importance that a member of the family takes over in the succession of the business, as he/she usually has a lifelong knowledge of the firm and a historical liaison with suppliers, clients and staff (Royer et al, 2008).…”
Section: Founder Legacymentioning
confidence: 99%
“…Harrison et al, 1991), and although family firms are the most common form of organizations throughout the world, accounting for over 75% of all registered companies in most economies (Miller, Steier & Le Breton-Miller, 2003), only few recent studies have focused on family firms' acquisitions (e.g. Feito-Ruiz & Menéndez-Requejo, 2010;Holmen & Nivorozhkin, 2007;Mickelson & Worley, 2003;Steen & Welch, 2006). A family firm is here defined as an organization in which a family has a substantial ownership stake, and has at least two of its members in key management positions (see Miller, Le Breton-Miller, Lester & Cannella, 2007;Westhead & Cowling, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…(Vaara, 2005), emphases that move from the prevailing culture perspective, being the dominate paradigm in studies of M & A integration towards new aspects. The firms who works on an international erena may need to kow more about mergeracquisition since most of direct investmants is by merger-acquisition (Steen & Welch, 2006). Some authors such as (Ben -Amar & Andre, 2006) stated that throug the family owership and the impact on value creation, the firm of business family can managed a harm any with the local culture and can have a higher level of long-run productivity, but if they have understand well the cultural assumptions of the social community (Astrachan, 1988) (Miller et al, 2010), reported inn their paper that there is more attention and need to distinguish between business risk and portfolio risk as their implications catiors for family firms acquisition.…”
Section: -2 : Cultural a Spects Of Post-merger-acquisitionmentioning
confidence: 99%